2022
DOI: 10.1002/cb.2122
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy and green consumption behavior: Exploring dual psychological mechanisms

Abstract: Green consumption has been developing into a booming trend due to alarming environmental problems. This study examines the relationship between the consumers' digital literacy and green consumption behavior and explores two different mechanisms based on social cognitive theory and self‐regulatory theory. The cognition‐based mechanism includes self‐efficacy and outcome expectation; the affect‐based mechanism includes anticipated pride and anticipated guilt. In addition, we investigate how green product availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 95 publications
3
21
0
Order By: Relevance
“…According to the Self-Consistency Theory, strong green self-efficacy, the belief in one's ability to engage in eco-friendly behavior, can translate into a stronger willingness to protect the environment (Hu and Meng, 2023 ), including purchasing green food, as consumers believe it benefits both personal health and the environment.…”
Section: Research Hypotheses and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Self-Consistency Theory, strong green self-efficacy, the belief in one's ability to engage in eco-friendly behavior, can translate into a stronger willingness to protect the environment (Hu and Meng, 2023 ), including purchasing green food, as consumers believe it benefits both personal health and the environment.…”
Section: Research Hypotheses and Theoretical Frameworkmentioning
confidence: 99%
“…Second, external environmental factors, including price, labeling, government, advertising, etc. (Zheng et al, 2022 ; Hu and Meng, 2023 ; Lu and Li, 2023 ). Third, psychological factors, including consumer attitudes, cognition, knowledge, and environmental concerns (Meinhold and Malkus, 2005 ; Pagiaslis and Krontalis, 2014 ; Zheng et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies (Pine and Gilmore, 1998;Hu and Meng, 2022), the effect of stimuli on consumers and self-regulation in marketing is mainly reflected in consumer response level, including consumers identification with brands or products (Enrique et al, 2008) and involvement or immersion (Jones et al, 2010) in marketing activities.…”
Section: Antecedents Of Consumer Responsementioning
confidence: 99%
“…Mallat (2007) observed that premium pricing impedes in getting new customers. Hu and Meng (2022) in the context of green products consumption argued that the lower product cost indirectly increases perceived benefits. Wu and Wang (2005) summed up that PFC has negative relation with BI.…”
Section: Moderation Effect Of Pfcmentioning
confidence: 99%